Circulation of copper and copper alloys in hinterland southern Africa: material evidence from Great Zimbabwe (1000-1700CE) - Mugabe, Bedone (Department of Archaeology, 2023)
This dissertation seeks to establish the possible provenance of copper and copper alloys used at Great Zimbabwe (1000-1700CE) to infer local and regional circulation circuits. It employs archaeological, archival, and geochemical methods to characterize samples of 26 wound wire bracelets, bangles, anklets, necklaces, and other forms of expressive and decorative wear excavated from the southern terrace, (Hill Complex) at Great Zimbabwe. The samples were macroscopically, microscopically, chemically and isotopically characterized to understand the technique of manufacture, chemical composition, lead isotopic ratios and the starting composition of uranium and thorium in relation the model ages. The Pb isotopic data calculated 238U/204Pb (μ), 232Th/ 238U(κ) ratios and estimated model ages (T) were compared with published lead isotopic ratios from various ore samples from central and southern Africa. Within opportunities afforded by the historical record and limitations imposed by small sample sizes especially of the comparative geology, indications are that the studied objects were produced using ores matching the Cu-Ni mineralization at Empress Mine (in Zimbabwe), Cu Ag and Cu Pb Zn Ag mineralization associated with the Kundelungu Plateau (bordering Zambia and Democratic Republic of Congo). This suggests that Great Zimbabwe participated directly and indirectly in the vibrant micro, regional and interregional circulation of copper and other resources. Future work, must however, add more trace element data from the objects and increase the number of samples from ancient mines and other sites to develop a fuller picture of the movement of copper in Iron Age southern Africa through space and time.